Analysis of substrate variations related to dinosaur track preservation from the Aguada de Tuco area, Candeleros Formation (Cenomanian), Neuquén Basin, Argentina - Heredia, Arturo Miguel (2018)
Fossil tracks provide direct information of the activity of a trackmaker during the interaction with the substrate. Track morphology can exhibit differences as a response to changes in substrate physical parameters like humidity, grain-size and sediment composition, as well as response to the limb dynamics and foot anatomy of the trackmaker. Recently, several dinosaur tracks with different preservational variants were found in a tracksite under study of the Candeleros Formation (Aguada de Tuco). An unusual narrow-gauge sauropod trackway preserved in fine-grained sandstones from floodplain deposits was documented. Each left track shows bulky and high (vertical) rims, significantly larger than the right ones. Thus a different substrate property between them is envisaged. These bulky rims also show well-preserved and non-deformed ripples on the top, suggesting a moist underlying substrate but with a dried or stabilised top that was only displaced upward during the track formation. The same stratigraphic surface contains a set of three extended tridactyl trackways, deeply impressed with no variation in the morphology of each track. In consequence no changes in substrate properties are interpreted between them. However, some discontinuous and shallow sauropod tracks were produced before the tridactyl trackways as they are overimprinted. Interestingly, 10 m apart a cluster of theropod trackways exhibit larger and shallower tracks than the previous one, which indicate a more consistent substrate, considering that they correspond to larger producers in the last case. In conclusion, the general track morphology is mainly conditioned by changes in substrate consistency over time in the same area.